2021
DOI: 10.1002/ajmg.a.62612
|View full text |Cite
|
Sign up to set email alerts
|

Extending the phenotype of posterior column ataxia with retinitis pigmentosa caused by variants in FLVCR1

Abstract: Posterior column ataxia with retinitis pigmentosa (PCARP) is a rare autosomal recessive condition due to variants in the Feline Leukemia Virus Subgroup C Cellular Receptor 1 (FLVCR1) gene which was first described in 1997. In this article, we describe a young female patient with a childhood diagnosis of retinitis pigmentosa and learning disability, presenting with progressive ataxia from her late teens. Examination revealed spastic lower limbs with absent reflexes, and reduced vibration and joint position sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…FLVCR1-mediated choline uptake is essential for life as its complete loss leads to embryonic lethality, suggesting that the salvage pathway cannot completely compensate in vivo. Similarly, patients with missense mutations in FLVCR1 present with posterior column ataxia and retinitis pigmentosa (PCARP), an autosomal recessive neurodegenerative syndrome characterized by loss of retinal function and subsequent degeneration of the posterior columns of the spinal cord from proprioception loss [10][11][12][13] . Interestingly, the photoreceptor cells of the retina have high affinity for choline and require an abundance of phospholipids to maintain the large membranous surface area of the outer segment [49][50][51] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FLVCR1-mediated choline uptake is essential for life as its complete loss leads to embryonic lethality, suggesting that the salvage pathway cannot completely compensate in vivo. Similarly, patients with missense mutations in FLVCR1 present with posterior column ataxia and retinitis pigmentosa (PCARP), an autosomal recessive neurodegenerative syndrome characterized by loss of retinal function and subsequent degeneration of the posterior columns of the spinal cord from proprioception loss [10][11][12][13] . Interestingly, the photoreceptor cells of the retina have high affinity for choline and require an abundance of phospholipids to maintain the large membranous surface area of the outer segment [49][50][51] .…”
Section: Discussionmentioning
confidence: 99%
“…1g). FLVCR1 is a plasma membrane transporter previously characterized as a heme exporter 9 and has been implicated in the rare autosomal-recessive disorder posterior column ataxia and retinitis pigmentosa (PCARP) [10][11][12][13] . CHKA catalyzes the production of phosphocholine through phosphorylation of choline.…”
Section: An Integrative Genetic Analysis Associates Serum Metabolites...mentioning
confidence: 99%
“…34 Sensory ataxia was a cardinal feature in the present patient characterized by loss of position sensation, apallesthesia, and a lack of cerebellar signs, which is described frequently in FLVCR1 gene-related diseases. 3,17 No abnormalities of brain MRI excluded a common cause, such as vascular, trauma, or tumor lesions. Additionally, this patient showed asymmetrical length-dependent sensory neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…5,9,[12][13][14][15][16] Most studies indicated patients had absent reflexes, a typical feature of peripheral nerve involvement. 17 Recently, sporadic sensoryautonomic neuropathy, 14,17,18 sensory ataxia, [19][20][21] sensory neuropathy, 22 pure retinitis pigmentosa 20 encephalopathy, 17 and nonsyndromic retinitis pigmentosa 20 are also described in FLVCR1 gene-related diseases. Sural biopsy confirmed loss of myelinated and unmyelinated fibers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation